(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Due to their distinctive electronic characteristics, multiple (2D) semiconductor materials have received a lot of interest from the electronic engineering community. Particularly, the inherent benefit of scaling semiconductors down to atomic thickness has sparked speculation of a potential Moore’s law extension. Given that semiconducting defect quantum mechanics play a crucial part in regulating the device conductivity of conductive polymers and functionalizing their devices, a thorough understanding of these fields is essential to the development of 2D electronics. In this paper, the author first discusses the significance of 2D semiconductors for Nano electronics and photodetectors. Second, we explain how electrical characteristics of 2D materials, such as ion concentration and their conductive type, are affected and controlled by native defects or deliberate impurities. The author concludes that several new theoretical approaches to assessing the ionization energies of imperfections and corresponding conductor type are described in detail in this part, along with technologies and platforms of faults. Third, common device tests are used to illustrate how faults directly affect the functionality of 2D electrical devices.